PENGARUH RELAKSASI BENSON TERHADAP PENURUNAN KECEMASAN PADA PASIEN AKUT MIOKARD INFARK (AMI) AKUT DI RUMAH SAKIT Hj. ANNA LASMANAH BANJARNEGARA - Tatang Kurniawan Setia Aji; Adiratna Sekar Siwi; Ikit Netra Wirakhmi (Jurnal Ilmiah Kesehatan Keperawatan, 2023)
Background: Acute Myocardial Infarction (AMI) is a life threatening condition due to the onset of chest pain, collapse and sudden death. The success of AMI treatment is very dependent on time, AMI also causes psychological problems in the form of anxiety. This study aims to determinethe effect of Benson's relaxation on reducing anxiety in patients with Acute Myocardial Infarction (AMI) at RSUD Hj. Anna Lasmanah Banjarnegara. Methods: The design of this study used an analytic correlation design with a cross sectional approach. By using pre and post test approach without control. The number of samples was 30 respondents. This study used the Hamilton Rating Scale for Anxiety (HRS-A) questionnaire in measuring anxiety. After measuring the patient's anxiety, benson relaxation was given and then the level of anxiety was measured again. Results: Prior to the Benson relaxation, the most respondents with severe anxiety were 14 respondents (46.7%). After the Benson relaxation, the respondents experienced a decrease in anxiety with a moderate category of 20 respondents (66.7%).Conclusion: The results showed that there was an effect of Benson relaxation on reducing anxiety in AMI patients at Hj. Anna Lasmanah Banjarnegara with p-value 0.00 (<0.05).